The intracellular nucleotide‐binding leucine‐rich repeat receptor (SlNRC4a) enhances immune signalling elicited by extracellular perception. (3rd July 2018) - Leibman‐Markus, Meirav; Pizarro, Lorena; Schuster, Silvia; Lin, Z.J. Daniel; Gershony, Ofir; Bar, Maya; Coaker, Gitta; Avni, Adi
Abstract: Plant recognition and defence against pathogens employs a two‐tiered perception system. Surface‐localized pattern recognition receptors (PRRs) act to recognize microbial features, whereas intracellular nucleotide‐binding leucine‐rich repeat receptors (NLRs) directly or indirectly recognize pathogen effectors inside host cells. Employing the tomato PRR LeEIX2/EIX model system, we explored the molecular mechanism of signalling pathways. We identified an NLR that can associate with LeEIX2, termed SlNRC4a (NB‐LRR required for hypersensitive response‐associated cell death‐4). Co‐immunoprecipitation demonstrates that SlNRC4a is able to associate with different PRRs. Physiological assays with specific elicitors revealed that SlNRC4a generally alters PRR‐mediated responses. SlNRC4a overexpression enhances defence responses, whereas silencing SlNRC4 reduces plant immunity. Moreover, the coiled‐coil domain of SlNRC4a is able to associate with LeEIX2 and is sufficient to enhance responses upon EIX perception. On the basis of these findings, we propose that SlNRC4a acts as a noncanonical positive regulator of immunity mediated by diverse PRRs. Thus, SlNRC4a could link both intracellular and extracellular immune perceptions. Abstract : Plant–microbe interactions involve a large number of regulatory systems essential for plant defence responses against biotic attack. Employing the tomato pattern recognition receptor (PRR) LeEIX2/EIX model system, we have identified a nucleotide‐binding leucine‐rich repeat (NB‐LRR) able to associate with LeEIX2, termed SlNRC4a. Our data suggest that SlNRC4a acts as a noncanonical NB‐LRR, positively regulating immunity mediated by diverse PRRs.